Results of surgical treatment of early-stage non-small cell lung cancer - Aškinis, Renatas; Krasauskas, Arnoldas; Zaremba, Sigitas; Cicėnas, Saulius (Lietuvos chirurgija, 2016)
The increasing incidence of lung cancer in Lithuania and in the world remains relevant to improving the effectiveness of treatment. Lung cancer is often diagnosed at an older age. Non-small cell lung cancer accounts for about 85%, and small cell lung cancer 15% of all diagnosed lung cancers. About 25% of newly diagnosed non-small cell lung cancer cases are stage I and II, in other cases, however, local or distant spread of lung cancer is detected, when surgical treatment is not indicated. Early-stage non-small cell lung cancer treatment start is radical resection, if the patient’s condition allows. After the operation, an adjuvant platinum–based chemotherapy is combined with etoposide. We analyzed 82 IB–IIIA non-small cell stage lung cancer sufferers who underwent radical resection in combination with a subsequent adjuvant chemotherapy. 1–2 of years after surgery disease progression was noted in 22 patients (27%), while in the 60 (73%) we observed disease remission. These findings stress necessity of additional DNA testing to individualize the treatment itself and improve treatment outcome.
Keywords: non-small cell lung cancer; surgical treatment; results